Efficacy of progressive resistance training intensities and adequate dietary protein intake for community-dwelling frail older adults (TEAMS study), protocol for a randomised controlled trial - M. Benali; J. van den Helder; E. J.M. Biersteker; J. D. Schoufour; P. J.M. Weijs; M. Tieland (BMC Geriatrics)
Abstract Background Progressive Resistance Training (PRT) and adequate dietary protein are crucial for preventing and managing sarcopenia and frailty in older adults. To date, the optimal intensity of PRT and the added value of dietary protein for enhancing muscle mass, strength, and physical performance in frail older adults remain unclear. This randomised controlled trial aims to determine the efficacy of various PRT intensities and adequate dietary protein intake in improving muscle mass, strength and physical performance in frail, community-dwelling older adults. Methods This study is a two-step randomised clinical trial involving 300 frail older adults. Participants will engage in a 12-week PRT twice weekly. Initially, participants will be randomised to specific training intensities, ranging from 20 to 80% of their one-repetition maximum (1-RM). Subsequently, participants will be further randomised into two groups: an intervention group receiving a dietary intervention targeting a daily protein intake of 1.2–1.5 g/kg/day (PRT-Pro), and a control group with no dietary intervention (PRT-only). The dietary protein intervention will include counselling sessions and the provision of protein-rich foods. Discussion This study aims to elucidate the effect of various PRT intensities and the supplementary effects of adequate dietary protein intake on muscle mass, muscle strength, and physical performance in frail older adults. The results will provide critical insights for scientists and healthcare professionals, facilitating the development of more effective strategies to combat sarcopenia and frailty in this population. Trial registration The trial is registered at the ICTRP (OMON trial ID NL8785).